2020
DOI: 10.1186/s13020-020-00333-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acupuncture in the prevention and treatment of chemotherapy-induced nausea and vomiting in patients with advanced cancer: a multi-center, single-blind, randomized, sham-controlled clinical research

Abstract: Background: Chemotherapy-induced nausea and vomiting (CINV) is a common and distressing side effect. We conducted this clinical trial to compare the effectiveness of true acupuncture vs. sham acupuncture in controlling chemotherapy-induced nausea and vomiting (CINV) among patients with advanced cancer. Methods: A total of 134 participants were randomly allocated into true acupuncture (TA) (n = 68) and sham acupuncture (SA) (n = 66) groups. Participants in both groups received acupuncture session twice on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
(30 reference statements)
0
13
0
2
Order By: Relevance
“…These effects were not observed during the acute phase. Recently, a randomized controlled study reported that acupuncture had a modest effect on reducing the severity of nausea and vomiting based on the Common Terminology Criteria for Adverse Events version 4.0 (CTCAE v4.0) in the delayed phase but not in the acute phase without statistical significance [ 21 ]. Similar to our findings, electronic acupuncture had a significant effect on nausea from the third day and on vomiting from the fourth day after the chemotherapy session compared to the sham acupuncture group, even though the complete response rate, which was the primary outcome, was not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were not observed during the acute phase. Recently, a randomized controlled study reported that acupuncture had a modest effect on reducing the severity of nausea and vomiting based on the Common Terminology Criteria for Adverse Events version 4.0 (CTCAE v4.0) in the delayed phase but not in the acute phase without statistical significance [ 21 ]. Similar to our findings, electronic acupuncture had a significant effect on nausea from the third day and on vomiting from the fourth day after the chemotherapy session compared to the sham acupuncture group, even though the complete response rate, which was the primary outcome, was not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. ( 39 ) used EA and acupuncture to stimulate acupoints during chemotherapy in patients with advanced cancer, finding that this not only reduced the severity of chemotherapy-induced nausea and vomiting during remission but also consistently improved the nutritional status of the patients after completion of chemotherapy. LA was also effective in reducing adolescent tumor patients’ nausea scores on days 1–5 after chemotherapy, with a significant reduction in the number of vomiting episodes on days 2 and 3, suggesting that low-frequency LA is effective in relieving delayed-phase CINV-related symptoms caused by chemotherapy in cancer patients ( 40 ).…”
Section: Efficacy and Mechanisms Of Acupoint Stimulation In The Allev...mentioning
confidence: 99%
“…Finally, 10 studies were excluded, and the remaining 18 studies were included in the review. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the 18 included studies, the sample sizes involved ranged from 30 to 120 with a total of 563 cases in the treatment group and 572 in the control group, which were all patients with or without post-chemotherapy nausea and vomiting. The process of the search, screening, and selection for the study is shown in Figure 1.…”
Section: Inclusion In the Study Screening Processmentioning
confidence: 99%
“…A total of 18 articles were included comprising two in English 10, 11 and 16 in Chinese 12-27 of which 10 were published in the past five yea rs, 11,12,14,17,22-27 six published in 2010-2016, 10,15,18-21 and one article published before 2010. 13 A total of 48 acupoints were selected from the 18 articles, of which the most frequently used was the Zusanli acupoint (ST36) with 563 times of adoption, accounting for 82.11% of the total, followed by the Neiguan acupoint (PC6) with 504 times, accounting for 44.40% of the total, and the third was the Zhongwan acupoint (CV12) with 270 times, accounting for 23.78% of the total, respectively.…”
Section: Documentation Characteristics Statisticsmentioning
confidence: 99%